AL-INÂYAH AND AL-IKHTIRÂ’ IN IBN RUSHD’S DIVINITY CONCEPT AND ITS RELEVANCE TO THE QURAN - Rofi'i, Muhammad Arwani; Arrois, Syaiful Makhi Ula; Hamzah, Muhammad Habibi; Saleh, Sujiat Zubaidi; Arif, Syamsuddin (Ulul Albab: Jurnal Studi Islam, 2025)
This article explores the application of the theories of al-Inâyah (Providence) and al-Ikhtirâ’ (Creation) as a Quranic approach. The analysis is based on Ibn Rushd’s Manâhij al-Adillah fî Aqâ’id al-Millah, highlighting how he integrates Greek philosophy with Islam to explain God as the First Cause and the Organizer of the universe. The method used is library research with a content analysis approach. The results show that Ibn Rushd views the order of the universe as a manifestation of God's will, where creation itself serves as evidence of a Creator with a divine purpose. The theories of al-Inâyah and al-Ikhtirâ’ are employed to argue that the universe’s order and complexity are the results of divine intention, in line with Quranic teachings about God as Creator and Organizer. This study finds that Ibn Rushd combines Aristotelian philosophy with Quranic teachings to provide a more comprehensive understanding of God. Using both reason and revelation, he portrays God as an essence that transcends the physical realm. The findings contribute to a deeper understanding on Islamic theology by showing the compatibility between rational inquiry and divine revelation. This study also demonstrates Ibn Rushd’s significant influence on both Islamic and Western philosophical traditions, reflecting a profound integration of philosophy and theology in conceptualizing the divine.